A Longitudinal Analysis of Facial Deformity in Cleft Lip Patients Before and After Lip Repair - NOZOE, Etsuro (Journal of Japanese Cleft Palate Association, 1988)
Anthropometric analysis was carried out on the soft tissue of the face in unilateral cleft lip patients. The subjects consisted of 37 CL (cleft lip with or without alveolar cleft) and 26 CLP (cleft lip, alveolus and palate). Fourteen points were selected and marked, then distances were estimated by slide calipers direct ly on the patient's face at pre- and post operation,2 weeks,1 month,3 months and 1 year after lip repair. The results were as follows: 1. The distance between the internal eye angles in CLP was significantly larger than that in CL. 2. In the presurgical stage, the lateral deviations of columellar base and nasal ala in non-cleft side were affected by the magnitude of cleft width. 3. The relapse-ratio of columellar base, which had been shifted correctly on the midline immediately after the operation, was 19 % in CL and 25 % in CLP after one year. The rapidity and degree of relapse w ere affected by the magnitude of cleft width. 4. Both lateral nasal alas, shifted medially after the operation relapsed the most in the first 2 weeks. After that, relapse tended to cease on non-cleft side but gradually continued on cleft side. 5. The marginal length of the naris on cleft side became longer than on non-cleft side 1 to 3 months after the operation. 6. The difference between vermillion border length on cleft side and on non-cleft side after the operation was approximately the same as before the operation. 7. In those cases with less difference between the lateral vertical lip length on cleft side and on non-cleft side before the operation, the vertical length on cleft side tended to become longer than on non-c left side after the operation.